PRODUKSI GAS OXYHYDROGEN (HHO) UNTUK GENERATOR SET DENGAN SUMBER ENERGI SURYA - Nurul Hidayah; Suryanto; Muhammad Aslam; Iffa Islamiayah, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The aim of this research is to determine the efficiency of the HHO generator and calculate the impact of using HHO gas in a generator set on specific fuel consumption (SFC). The research was carried out using experimental methods to test the performance of Wet Cell Type and Dry Cell Type HHO generators using an electrolysis process with variations in NaOH concentration and input power. The DC electrical energy source for the electrolysis process comes from Photo Voltaic (PV) panels. The HHO gas produced by the HHO generator is used as additional fuel to run an electric generator. The test results show that the efficiency value of the wet cell and dry cell HHO generators is influenced by the percentage of NaOH concentration. The highest efficiency value produced was found at a NaOH concentration percentage of around 7.7%. The dry cell type HHO generator produces almost the same efficiency compared to the wet cell type HHO generator. Where the HHO Dry Cell Type generator has the efficiency of 67% while the HHO Wet Cell Type generator 66%. In testing the use of HHO gas used in a generator set, HHO gas can reduce the use of fuel, indicated by the decrease in SFC.